Transfer Pricing, A Tax Avoidance Tool (A Review of Literature) - Delina Herdian Septiani; Ida Farida Adi Prawira; Memen Kustiawan (Nusantara Science and Technology Proceedings, 2020)
The purpose of the work presented in this paper is to capture the current state of Transfer Pricing as well as to document the current practices of Transfer Pricing Abuse through a systematic literature review to extend and update the previous work. The approach to this paper is to answer the questions such as “what is Transfer Pricing?”, “How is it progressing?”, “what are the driving factors?” and “what are the emerging trends?”. These questions are used to guide the search of papers from various publication databases even if it is expected that existing literature might not be sufficiently developed to translate each question directly into a finding. The literature is then analyzed and the major emerging themes are presented. Four key findings (topics on which the views of the authors converged) and two issues (topics on which authors had differing views) have been established. These include the interpretation of Transfer Pricing, Arm’s Length Price Principle, Transfer Pricing methods, and Transfer Pricing as a tax avoidance technique. The systematic literature review approach used in this paper allows emerging trends and issues in Transfer Pricing to be highlighted in a structured and thematic manner. These findings also open up information about transfer pricing issues so that they can be used as reference material for further research.